1999
DOI: 10.1165/ajrcmb.20.4.3390
|View full text |Cite
|
Sign up to set email alerts
|

Role of a Novel KCa Opener in Regulating K+ Channels of Hypoxic Human Pulmonary Vascular Cells

Abstract: Hypoxic pulmonary vasoconstriction (HPVC) is mediated, in part, via membrane depolarization and inhibition of K+ channels. We recently observed that the naturally occurring steroid dehydroepiandrosterone (DHEA) reversed and prevented HPVC in isolated perfused and ventilated ferret lungs. In the current study, we investigated the effects of DHEA on the major K+ channels of chronically hypoxic human pulmonary smooth-muscle cells (HPSMC). K+ channels were recorded by using the patch-clamp technique in whole-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 17 publications
0
34
1
Order By: Relevance
“…In contrast, it has been shown that acute hypoxia could inhibit canine and fetal ovine PASMC K Ca channels (11,36). In addition, chronic hypoxia decreased CTX-sensitive K Ca channels in human PASMC (32). In our murine model, perinatal exposure to hypoxia results in increased BK Ca channel activity and protein content in adults.…”
Section: Discussionmentioning
confidence: 56%
“…In contrast, it has been shown that acute hypoxia could inhibit canine and fetal ovine PASMC K Ca channels (11,36). In addition, chronic hypoxia decreased CTX-sensitive K Ca channels in human PASMC (32). In our murine model, perinatal exposure to hypoxia results in increased BK Ca channel activity and protein content in adults.…”
Section: Discussionmentioning
confidence: 56%
“…This leads to a deep change in the PA properties, and PA from CH rats do not respond to further acute hypoxic stress. DHEA has been characterized by Peng et al (13) as a BK Ca channel opener at 100 M. IPA rings from CH-DHEA animal develop higher reactivity to IbTx, which blocks K Ca as compared with CH rats, suggesting an involvement of the BK Ca in the control of IPA basal tone from CH-DHEA rats. Furthermore, in smooth muscle cells from CH-PHT rats, acute exposure to DHEA induced a decrease of the resting [Ca 2ϩ ] i that is blocked by IbTx.…”
Section: Discussionmentioning
confidence: 99%
“…We sought to enhance expression and function of BK Ca by using DHEA, a BK Ca opener in hypoxic human pulmonary cells (13), which can shift the redox balance toward an oxidized state leading to both BK Ca and Kv activation and thus repolarization of the PASMCs membrane potential and its effects on the [Ca 2ϩ ] i. In vivo PA pressure (PAP) as well as right ventricular (RV) wall thickness were measured in closed-chest rats undergoing CH.…”
mentioning
confidence: 99%
“…(Figure 1), DHEA was hypothesized to have vasodilating properties. DHEA was found to efficiently inhibit hypoxic pulmonary vasoconstriction, at least in part by opening BK Ca channels in pulmonary VSMCs [60][61][62]. Western Blot analysis of arterial pulmonary extract showed that the BK Casubunit expression is upregulated after DHEA treatment compared to chronic hypoxia rats [63].…”
Section: Dhea Vasodilating Propertiesmentioning
confidence: 99%